A Sociosemiotic Analysis of Fugard’s My Children! My Africa! - Viator, Timothy J. (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2016)
This essay presents a sociosemiotic analysis of My Children! My Africa! (1989) by Athol Fugard. By considering the characters’ views about self, community, education, and time, it points to the Fugard’s anxious attempt to offer liberalism as the solution to apartheid in South Africa instead of oppositional politics, especially blacks’ calls for activism and communalism. Sociosemiotics is suitable to plays overtly political; it holds that political writers are troubled by political changes that do not correspond to a firmly held ideology—a tension between what a playwright believes is absolute and what s/he senses and perhaps fears is happening. Keys to the analysis are contemporary texts, including essays from leading Black writers and journalists and from studies and essays from attendees of a 1986 conference on liberal solutions to the unrest in South Africa.